2013
DOI: 10.5301/ejo.5000272
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of Prematurity: A Nationwide Survey to Evaluate Current Practices and Preferences of Ophthalmologists

Abstract: This survey reveals considerable variation among Turkish ROP specialists regarding ROP care. The survey data are critical in order to develop quality improvement and help in planning more effective future programs for ROP care in terms of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Access to ROP screening is limited due to the need for highly specialized personnel and the time-consuming nature of its clinical practice, as well as significant associated medicolegal risk 6,7. Screening examinations have traditionally been carried out by a trained ophthalmologist using a binocular indirect ophthalmoscope.…”
Section: Introductionmentioning
confidence: 99%
“…Access to ROP screening is limited due to the need for highly specialized personnel and the time-consuming nature of its clinical practice, as well as significant associated medicolegal risk 6,7. Screening examinations have traditionally been carried out by a trained ophthalmologist using a binocular indirect ophthalmoscope.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 1100 to 1500 progress to severe disease requiring medical intervention. 1,2 Cryotherapy has traditionally been the treatment of choice. However, during the last 2 decades, there has been a general shift in treatment of ROP to favor laser photocoagulation surgery or intravitreal injection of vascular endothelial growth factor inhibitors over cryotherapy owing to fewer side effects and more positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the last 2 decades, there has been a general shift in treatment of ROP to favor laser photocoagulation surgery or intravitreal injection of vascular endothelial growth factor inhibitors over cryotherapy owing to fewer side effects and more positive outcomes. [2][3][4][5] Even though laser photocoagulation surgery has been commonly used for over 20 years, there is not a widely accepted guideline regarding sedation during the procedure. It may be performed in an operating room under general anesthesia or at the bedside under intravenous (IV) sedation.…”
Section: Introductionmentioning
confidence: 99%
“…There are two ways to ensure adequate sedation and analgesia during laser photocoagulation procedures: general anaesthesia with patients intubated and ventilated or sedation plus analgesia with the patient breathing spontaneously or receiving noninvasive respiratory support. Studies have reported that approximately one in two centres interviewed adopted general anaesthesia, while the remainder opted for sedation plus analgesia in the NICU . General anaesthesia enables the newborn infant to be kept perfectly immobile, which is appreciated by ophthalmologists and allows for much longer operating times.…”
Section: Introductionmentioning
confidence: 99%